Effect of Bamboo Leaves Extract Concentration (Dendrocalamus sasper L.) as Bioherbicide on Nutsedge (Cyperus rotundus L.) - Nur Hidayatullah (International Journal of Science, Engineering, and Information Technology, 2019)
Cyperus rotundus one cause of the decline in crop production due to the nature of parasitism in plants cultivation. Cyperus rotundus including important weeds in various types of plants that can cause reduced farming production. The use of chemical herbicides continuous and not wisely, today raises many problems, especially in environmental pollution and health. Alternatives that are used to control weeds in addition to using bioherbisida is with bamboo leaf ekstrrak (Dendrocalamus sasper) containing phenolic compounds, coumarin and flavonoids. Based on the results of previous studies, the use of biohersida quite effective in controlling Cyperus rotundus. In this study will test the effectiveness of bamboo leaf extract (Dendrocalamus sasper) against Cyperus rotundus. The study used a completely randomized design (CRD) 7 treatments with 5 replicates. Research that has been carried out bamboo leaf extract (Dendrocalamus sasper) capable mengperhambat growth of sedges, it is evident from the parameters is done on research that has been carried out. Of the various parameters of observation, bamboo leaf extract treatment with a concentration of 90% real effect on all parameters and is the most effective treatment of all treatments.